Using the Scenarios of Simulation Case Assignments in the Educational Process of Students in the Specialty "State and Municipal Management", Master’s Degree Programme - Urzha, Olga; Kataeva, Valentina; Evstratova, Tatiana; Zhukova, Valentina; YIlina, Irina (International Journal of Engineering and Technology, 2018)
The article is devoted to the use of simulation case assignments in the learning process of students pursuing a Master's degree in "State and Municipal Management" at Russian State Social University. This university was established in 1991 for the high-quality training of specialists in the social sphere. The specialty "State and Municipal Management" enables students to explore the theoretical and practical levels, the essence and features of management interactions in the system of state and municipal administration, the main objectives, tasks and mechanisms of governance at the state and municipal levels, the methods and means of attracting investments in the economy of the municipality and the region, the features of the management system of the asset portfolio. The discipline "Sociology of Management" is the base for the direction of training "State and Municipal Management". The knowledge and skills acquired during the study contribute to a better understanding of the social, political, and economic patterns of management processes. Management sociology is a science which summarizes all management sciences in terms of targeting and special study of the patterns of managerial relations at all levels of society and its elementsâ€™ functioning, as well as in all subject areas, the spheres of activity in society. The study of sociology as a science about relationships in the process of governance, connections, and interactions of the subjects of management activity in Russia has started relatively recently. In the mid-1990s, scientific readings and conferences were focused on the definition of the substantive field of science, its structure.Over these years, the situation has been as follows. The sociologists who violently debated and developed this scientific direction, after the appearance of the specialty "Management in Social Sphere" in 1996, in 1999 â€“ the specialty "State and Municipal Management", and in 2002 â€“ the specialty "Personnel Management", handed the study of this discipline to managers. And all of these management specialties found themselves in the consolidated group of professions "Economics and Management". This greatly affected the gap in the subject field of management itself. Most economists imagined that management is economics. The lawyers of those universities where departments of "Public Administration and Legal Support" were established never doubted that management is a legal sphere of activity. None of them paid special attention to the sociological component. However, those universities, which in the course of training in the field of state and municipal government created departments of sociology management in their structure or modules in the curricula, provide the most high-quality preparation of future managers.Â Â